(untitled) - Havel, Karel; Novak, Andrej; Pitor, Jan (Doprava a spoje, 2011)
The aim of this paper is provision of information regarding primary radar flight checking to the aviation community. It deals with the usage of Sliac airport surveillance radar and provides an overview of the surveillance radar flight checking in the Slovak Republic. This paper was written under project Centre of Excellence for Air Transport ITMS 26220120065 cofinanced by the EU, which supports research activities in Slovakia.